2018
DOI: 10.15406/bij.2018.02.00058
|View full text |Cite
|
Sign up to set email alerts
|

Ecological status for Ratapani wild life sanctuary, Raisen (MP) India

Abstract: The baseline study was conducted for the evaluation of the floral and faunal biodiversity of the terrestrial as well as aquatic environment of the study area, it comprises of total 5reserved forest and 3 protected forest including Ratapani Wildlife Sanctuary falls Dist.-Raisen, Madhya Pradesh, India. It is strongly recommended to prepare the conservation plan for schedule-1 Fauna (listed 9 animals and 1 bird) and it is ensure to implement the conservation plan during construction and operation phase of railway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The phase-1 result (Figure 9a) revealed that in the northern part of the study area (shown in red-toyellow colour in Figure 9a), the second epoch (2006)(2007)(2008)(2009)(2010) received less rain than the first epoch (2001)(2002)(2003)(2004)(2005). Interestingly, a similar pattern was observed in NDVI difference, i.e., In fact, these areas are drier regions with scrubs, grasses and thorn vegetation types [68][69][70] and especially lantana camara, which have covered most parts of the protected forests of central India [68,71]. Apart from this, the region is abundant with teak forests [69,72] with low biomass accumulation, which is limited due to environmental conditions compared to other moist forests.…”
Section: Periodic (5 Yearly) Rainfall and Vegetation Sensitivitymentioning
confidence: 59%
See 2 more Smart Citations
“…The phase-1 result (Figure 9a) revealed that in the northern part of the study area (shown in red-toyellow colour in Figure 9a), the second epoch (2006)(2007)(2008)(2009)(2010) received less rain than the first epoch (2001)(2002)(2003)(2004)(2005). Interestingly, a similar pattern was observed in NDVI difference, i.e., In fact, these areas are drier regions with scrubs, grasses and thorn vegetation types [68][69][70] and especially lantana camara, which have covered most parts of the protected forests of central India [68,71]. Apart from this, the region is abundant with teak forests [69,72] with low biomass accumulation, which is limited due to environmental conditions compared to other moist forests.…”
Section: Periodic (5 Yearly) Rainfall and Vegetation Sensitivitymentioning
confidence: 59%
“…In the first epoch (the driest period in 18 years), the mean NDVI values were consistently smaller in the larger part of the north-western region (Figure 8a), which is a clear indication of the adaptation of vegetation systems in low-rainfall areas. In fact, these areas are drier regions with scrubs, grasses and thorn vegetation types [68][69][70] and especially lantana camara, which have covered most parts of the protected forests of central India [68,71]. Apart from this, the region is abundant with teak forests [72,69] with low biomass accumulation, which is limited due to environmental conditions compared to other moist forests.…”
Section: Periodic (5 Yearly) Rainfall and Vegetation Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The internal transcribed spacer sequence showed maximum similarity to sequences KU926333 and MK351861, as shown in . MK351861 was isolated from soil at Ratapani wildlife sanctuary in Raisen, Madhya Pradesh [18]. Sequence KU926333 was isolated from the lung biopsy sample of a fatal case of pulmonary mucormycosis in a patient with unchecked diabetes mellitus from Paris [19].…”
Section: Discussionmentioning
confidence: 99%
“…The status of individual species was assessed using the revised IUCN/SSC category system. [27][28][29][30][31][32][33][34][35] Figure 1 Study area Map.…”
Section: Secondary Data Collectionmentioning
confidence: 99%